(untitled) (American Journal of Islam and Society, 2023)
This paper focuses on maṣlaḥah (benefit or well-being) and adab (righteous behavior or character) as ethically intertwined concepts that are discussed by classical Muslim scholars in relation to the acquisition of wealth (kasb) and overall economic engagement. Particularly in certain works of al-Shaybāni (d. 805), al-Muḥāsibī (d. 857), Ibn Abī al-Dunyā (d. 894), al-Māwardī (d. 1058), and al-Ghazālī (d. 1111), personal piety is closely related to righteous economic behavior under the banner of adab’s moral stipulations. In light of al-Ghazālī’s understanding of economic provision as part of his overall theory of eternal happiness (saʿādah), the concept of maṣlaḥah can be analyzed in the context of adab as an extension of Sharīʿa law. While maṣlaḥah is from a legal standpoint crucial for safeguarding economic activities and preserving wealth, concomitantly, in this paper I treat maṣlaḥah as a derivative of adab and its holistic vision of human nature. In particular, I address what constitutes economic provision as an ethical endeavor in selected classical texts; and how the concept of adab preserves and enhances economic behavior as conceived by classical Muslim scholars.